The effect of additive type and ratio on the compaction parameters of high plasticity clay - Aslan, Yasemin; Gürocak, Zülfü (Dicle Üniversitesi, 2022)
Stabilization, which is defined as the improvement of the geotechnical properties of clayey soils by using additives with pozzolanic properties, is highly preferred today because it is easy to apply, economical and many of them are environmentally friendly. As a result of the textural changes that occur after successful stabilization by adding different pozzolans to the clayey soils, the optimum water content value, which is called the compaction parameters of the soil, increases, while the maximum dry unit weight decreases. In this study, the effects of additives used in different types and ratios on the compaction parameters of high plasticity bentonite were investigated. For this purpose, samples with additives using slaked lime, fly ash, acidic and basic tuffs in different proportions were prepared and Standard Proctor tests were carried out on these samples. According to the results obtained from the studies, the best results were obtained in the case of using only one additive material, in the sample with 5% acidic tuff and in the sample with 10% slaked lime. In the examples where two types of additives were used together, the best results were obtained in the example where 10% acidic tuff and slaked lime were used together. The results obtained from this study show that the best results are obtained in compaction parameters, especially when slaked lime and acidic tuff additive are used together.

Puzolanik özeliğe sahip katkı malzemeleri kullanılarak killi zeminlerin geoteknik özelliklerinin iyileştirilmesi olarak tanımlanan stabilizasyon, kolay uygulanabilir, ekonomik ve birçoğunun çevre dostu olması nedeniyle günümüzde çok fazla tercih edilmektedir. Killi zeminlere farklı puzolanlar katılarak başarılı bir stabilizasyon sonrasında oluşan dokusal değişimler sonucunda zeminin kompaksiyon parametreleri olarak adlandırılan optimum su içeriği değeri artarken, maksimum kuru birim ağırlığı ise azalmaktadır. Bu çalışmada, farklı tür ve oranda kullanılan katkı malzemelerinin yüksek plastisiteli bentonitin kompaksiyon parametreleri üzerindeki etkileri incelenmiştir. Bu amaçla katkı malzemesi olarak sönmüş kireç, uçucu kül, asidik ve bazik karakterli tüflerin değişik oranlarda kullanıldığı katkılı örnekler hazırlanmış ve bu örneklerde Standard Proktor deneyleri gerçekleştirilmiştir. Yapılan çalışmalardan elde edilen sonuçlara göre, sadece bir katkı malzemesinin kullanılması durumunda en iyi sonuçlar %5 asidik tüf katkılı örnekte ve %10 sönmüş kireç katkılı örnekte elde edilmiştir. İki tip katkı malzemesini birlikte kullanıldığı örneklerde ise en iyi sonuçlar %10 oranında asidik tüf ve sönmüş kirecin birlikte kullanıldığı örnekte ortaya çıkmıştır. Bu çalışmadan elde edilen sonuçlar, özellikle sönmüş kireç ve asidik tüf katkısının birlikte kullanılması durumunda kompaksiyon parametrelerinde en iyi sonuçların elde edildiğini göstermektedir.
Katkı türü ve oranının yüksek plastisiteli kilin kompaksiyon parametrelerine etkisi